2015
DOI: 10.1371/journal.pone.0129718
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intracoronary versus Intravenous Administration of Tirofiban during Percutaneous Coronary Intervention for Acute Coronary Syndrome: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundPercutaneous coronary intervention (PCI) is known as the most effective treatment for acute coronary syndrome (ACS). However, without proper therapy and patient management, stent thrombosis after PCI may lead to another myocardial infarction. In addition to aspirin and clopidogrel, tirofiban is often used as an antiplatelet therapy in patients with ACS. To date, there has been no comprehensive evaluation of the efficacy and safety of intracoronary (IC) tirofiban administration for ACS patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Moreover, a meta-analysis showed that compared with intravenous administration of tirofiban, intracoronary administration of tirofiban significantly increased TIMI grade 3 flow (odds ratio [OR] = 2.11; 95% CI 1.02–4.37; P = .04) and TMP grade 3 flow (OR = 2.67; 95% CI 1.09–6.49; P = .03, I 2 = 64%) while reducing the incidence of MACEs (OR = 0.46, 95% CI: 0.28–0.75; P = .002) in ACS patients. [31] Intraregional administration yielded favorable outcomes in terms of myocardial tissue reperfusion as evidenced by the improved TIMI flow grade, reduced incidence of cardiac thin filament complex (CTFC), complete ST-segment resolution, and reduced incidence of MACEs without an increase in the incidence of in-hospital major bleeding events. The intralesional administration of GPIs can be recommended as the preferred regimen to guard against no-reflow.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analysis showed that compared with intravenous administration of tirofiban, intracoronary administration of tirofiban significantly increased TIMI grade 3 flow (odds ratio [OR] = 2.11; 95% CI 1.02–4.37; P = .04) and TMP grade 3 flow (OR = 2.67; 95% CI 1.09–6.49; P = .03, I 2 = 64%) while reducing the incidence of MACEs (OR = 0.46, 95% CI: 0.28–0.75; P = .002) in ACS patients. [31] Intraregional administration yielded favorable outcomes in terms of myocardial tissue reperfusion as evidenced by the improved TIMI flow grade, reduced incidence of cardiac thin filament complex (CTFC), complete ST-segment resolution, and reduced incidence of MACEs without an increase in the incidence of in-hospital major bleeding events. The intralesional administration of GPIs can be recommended as the preferred regimen to guard against no-reflow.…”
Section: Discussionmentioning
confidence: 99%
“…Previous RCTs and meta-analyses have reported that, in patients with ACS, IC administration of GPI resulted in greater blood flow restoration and a better prognosis postoperatively than IV (intravenous) administration. Besides, IC administration did not lead to increased bleeding events, which are commonly observed with IV administration ( 24 - 29 ). Sun et al ( 30 ) demonstrated that IC administration did not provide optimal contact between GPIs and lesions in patients with ACS during PCI.…”
Section: Discussionmentioning
confidence: 83%
“…The utility of tirofiban in patients with STEMI has been investigated in several trials [6,10,11,[23][24][25]. These studies have evaluated both the 10 mcg/kg bolus and the high-dose bolus regimens.…”
Section: Discussionmentioning
confidence: 99%